Karakteristik Lahan Sawah yang Dialih Fungsi Menjadi Lahan Perkebunan di Desa Tangga Batu Kecamatan HatonduhanKabupaten Simalungun - Azis Syahed; Kemala Sari Lubis; Razali Razali (Universitas Sumatera Utara, 2015)
At Latest ten years, the paddy land at Tangga Batu area is use changed into plantation. This research was conducted to study characteristics of soil at some land uses ( paddy, rubber- cacao, and palm of 1,5 and 10 years old ).Soil sampling is conducted by using survey method. Soil samples are taken as soil sample disturbed and non distrubed at three (3) points in eachs land use randomly. The result showed that there is decreasing of total nitrogen at plantation and increasing of P- available at mixed farm (rubber – cacao). There are no changes of soil characteristics such us like potassiumexchange, pH, soil permeability, soil texture, and soil respirationat some land uses ( paddy, rubber- cacao, and palm of 1,5 and 10 years old ).Keywords: soil characteristics,agriculture land conversion.